Financial Measures for Electric Vehicles:Supporting the Integration of Renewable Energy in the Mobility Sector in Germany - Bickert, Stefan (International Journal of Renewable Energy Development, 2014)
Electric vehicles (EV) are able to support the transition of sectors towards sustainability. The operation of these vehicles with renewable energies saves local and global emissions. Furthermore, fluctuating renewable energies can be integrated in existing energy systems by using electric vehicles for grid services. Thus, implementation of advantages requires market establishment of electric vehicles. The article provides a review on potentials of market development by comparing and studying costs of electric and conventional vehicles as well as effects of financial measures on costs of EV. These cost comparisons are based on market data and predictions of cost developments for private consumers in Germany. Costs are analysed by an economic model of Total Cost of Ownership (TCO), aiming to display financial proportionality between vehicles in different years of acquisition (2010 to 2030). In a further step, external financial measures are analysed and integrated in the cost model as one possibility to enhance and secure the market introduction. Findings demonstrate that higher costs of acquisition of electric vehicles cannot be compensated by lower costs of operation. While mobility costs of conventionally vehicles stay constant or even increase during the considered years, mobility costs of electric vehicles significantly decrease especially in the upcoming years. In all cases mobility costs of electric vehicles exceed costs of conventional vehicles, but differences are reduced from 19â‚¬ct in 2010 to 3â‚¬ct in 2030. Cost decreases of the battery have high influence on the increasing financial comparability of EV. Concerning financial measures especially a differentiation of energy prices and a compensation of grid services can help to decrease total costs of EV and to manage a shift from fossil energy resources to electricity in the mobility sector. The existing tax exemption for EV compensates only a little fraction (about 6%) of the cost difference. This highlights the importance of research on incentive schemes to support market integration of EV and thereby the integration of renewable energies in the mobility sector. This integration is supported by the possibility of storing surplus fluctuating renewable energy in the batteries of EV.